Relationships Between Living Arrangements and Health Status Among Older Adults in the United States, 2009-2014: Findings From the National Health Interview Survey. (January 2018) - Weissman, Judith D.; Russell, David
Limited research has examined how health varies across living arrangements among older adults. Adults aged 65 years and older were sampled from National Health Interview Survey 2009-2014. Four indicators of health (serious psychological distress, health status, functional limitations, and number of health conditions) were compared across older adults living alone, living with others related/unrelated, living with a spouse/partner (no children), and living with children (no spouse/partner). Regression models showed older adults living with others have the poorest health; they were less likely to report excellent or very good health, had serious psychological distress and limitations in activities of daily living (ADLs), and a greater number of health conditions compared with older adults living with a spouse/partner. However, older women living alone or with children were more likely to report two or more health conditions compared with women living with a spouse/partner, suggesting that in older age, there are gender variations in health across living arrangements.